Endophytes from Ginkgo biloba and their secondary metabolites - Zhihui Yuan (Chinese Medicine, 2019)
Abstract Ginkgo biloba is a medicinal plant which contains abundant endophytes and various secondary metabolites. According to the literary about the information of endophytics from Ginkgo biloba, Chaetomium, Aspergillus, Alternaria, Penicillium and Charobacter were isolated from the root, stem, leaf, seed and bark of G. biloba. The endophytics could produce lots of phytochemicals like flavonoids, terpenoids, and other compounds. These compounds have antibacteria, antioxidation, anticardiovascular, anticancer, antimicrobial and some novel functions. This paper set forth the development of active extracts isolated from endophytes of Ginkgo biloba and will help to improve the resources of Ginkgo biloba to be used in a broader field.